Time Matters: Conceptual and Methodological Considerations in Translation Timescapes - Wakabayashi, Judy (chronotopos – A Journal of Translation History, 2019)
Time is a fundamental concept and context in translation history that merits more specific consideration than it has generally been accorded by translation scholars. This paper examines conceptual issues surrounding time, such as culture-specific time consciousness and teleological, linear and circular concepts of time, as well as change and continuity. It also explores some methodological issues relating to the treatment of time when writing translation histories, with a special focus on the principles and problems of periodization and how to structure narratives, including non-periodizing principles. Fernand Braudel’s three timescales of historical analysis are considered in terms of translation history, and the affordances of digital history in relation to time issues are also introduced. The paper concludes with a brief cautionary note about anachronistic interpretations and the compression of time when studying recent history.